PELATIHAN PEMANDU ACARA UNTUK MENDUKUNG PENYELENGGARAAN EVENT WISATA DI DESA TULUS BESAR - Hilda Cahyani; Alvin Nouval; Pritantina Yuni Lestari; Mariana Ulfa Hoesny; Isnaini Nur Safitri (Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program aimed to enhance the public speaking and event-guiding skills of local residents in Tulus Besar Village, Tumpang District, Malang Regency. The village holds significant natural and cultural tourism potential but lacks trained human resources capable of effectively promoting and managing tourism events. The program was carried out in five stages: planning, coordination with partners, interactive training, evaluation, and publication. A participatory approach involving discussions, simulations, and role-play activities was applied to improve the participants’ practical communication skills. The results indicated an increase in participants’ confidence and speaking competence in tourism contexts, despite several challenges, including limited participant numbers, basic technical facilities, and scheduling constraints. Based on the evaluation and literature review, the training proved effective in supporting community-based tourism development. Further action is recommended through advanced training, facility improvement, and integration with local art and cultural programs to ensure sustainability.